Desenhos infantis como ferramenta de análise da percepção sobre o meio ambiente - Prestes, Dirce Coronado (2021)
Elementary school students have difficulties in understanding the complexity of issues addressed in environmental education (EE). Based on several published works, it is possible to see the art as a great ally in the assessment of the perception of environmental problems. Thus, in this work it is applied drawing evaluation method, in order to verify the perception of the concept of the environment by fifth-grade students, correlating this perception to the trends of EE. The research was carried out in three stages with three classes elementary school at a municipal school in Santa Helena, PR. In the first stage, students were encouraged to freely draw what they understood about the environment, without any kind of intervention from researchers (First Test). In the second stage, classes and workshops about environment themes were given, covering topics such as the hydrological cycle, sustainability, solid waste and consumption, using a critical-emancipatory EE trend. In the third stage, the students were again encouraged to draw pictures about the environment (Second Test), in order to verify whether the intervention was able to change the perception of the respondents. The items represented in the drawings were categorized into biotic and abiotic elements, representations of humans, and human constructions, according to the DET methodology described in the literature. The frequency with which the categories appeared in the drawings was assessed using descriptive statistics and one-way ANOVA analysis of variance, followed by the Bartlett’s test, while the total score of the DET method was assessed using the Student’s t-test. The correlation with the EE trends was evaluated by the VET method developed in this research. In the First Test were analysed 62 drawings, and 36 in the Second Test. The representation abiotic and biotc elements were very frequent, while of humans and human constructions were less frequent. This result showed that the concept of the environment was confused with the concept of nature by the students, and the drawings were mainly related to the conservationist aspect of EE. After the didactic interventions, it was possible to notice an increase in the complexity of the relationships between the represented elements. This increase was statistically significant, with a mean total DET score of 4.77 ± 0.24 in the First Test and 5.55 ± 0.50 in the Second Test. Similarly, there was a change in the relationship between the drawings and the EE trends, with a decrease in drawings related to the conservationist trend (68% to 56%) and an increase in the drawings related to the pragmatic trend (26% to 31%) and critical- emancipatory (6% to 14%). Thus, the results indicated that most students have a vision linked to the conservationist aspect of EE and that didactic interventions focused on the critical-emancipatory aspect is able to change this view, making students develop values capable of forming citizens with abilities for discussing and solving environmental problems, as recommended by the National Policy on Environmental Education. In addition, the research showed that the DET method can be a useful tool to be used by teachers to assist them in assessing students' understanding of the concept of environment.